Cervical cancer prevention training in South East Asian LMICs - Joseph Soon-Yau Ng; Ida Ismail-Pratt (Elsevier, 2017)
The Association of Southeast Asian Nations (ASEAN) is a confederation of 10 sovereign states occupying approximately 1.7 million square miles of Southeast Asia with an estimated population of just under 630 million. Southeast Asia continues to have one of the world's highest rates of cervical cancer-related death. Organised training in cervical cancer screening is essential but lacking in low to middle income countries (LMICs). Systematic training of local doctors is an essential part of an effective screening program and an effective strategy to reduce cervical cancer-related mortality. Singapore is a first-world economy with a healthcare system that can support this mode of training and is geographically proximate to Southeast Asian LMICs that need this training. This makes it possible for model of tiered training with trainers on site in the LMICs and more advanced training where trainees receive training in Singapore. We present a case study where this tiered system of training is applied to Cambodia and demonstrate that this model of training is not only effective but also sustainable.